Design of personal protective equipment: to promote of Brazilian artifacts with ergonomic attributes - Leite, Charles; Guarnetti dos Santos, Joao Eduardo [UNESP]; Miranda, Ana Paula de; Santos Filho, Abilio Garcia dos [UNESP]; Arezes, P.; Baptista, J. S.; Barroso, M. P.; Carneiro, P.; Costa, N.; Melo, R.; Miguel, A. S.; Perestrelo, G.; et al. (Portuguese Soc Occupational Safety & Hygiene, 2013)
This research aims to investigate a topic sometimes overlooked among the research of ergonomics. Particularly, we treat the garments as personal protective equipment. In this study we abode on clothing produced and used in Brazil, making notes about the management of occupational safety for the use of such equipment. In turn, identify Relevant requirements for the design of personal protective equipment used in Brazil, in line with what is being studied in global forums on the subject.
Keywords: Fashion Design; Protective Clothing; PPE; Safety workplace; project requirements